Geotechnical investigation of soft clay for Bangkok airport - Chinawat Muktabhant (1983)
The study presents the properties of the subsoil along the new runway of the Don Muang International Airport. The soil consists of a series of alluvial clays. The top soil is about 1 meter thick. Beneath it is a very soft clay which has a high compressibility. The computation of settlement has been made by using the summary of the subsoil properties from Krungthep Engineering Consultants Co. Ltd. The improvement of the soil before the pavement construction have been determined by using sand drains and prefabricated drains. Estimation was made to compare the cost of the soil improvements with without soil improvements but overlay the concrete on top of the pavement after 5 and 12 years.
Thesis (M.S.)--University of the Philippines, Diliman
Keywords: Soil mechanics; Airports -- Runways. -- Thailand -- Bangkok; Soil consolidation